2007
DOI: 10.1097/01.ta.0000251558.38388.47
|View full text |Cite
|
Sign up to set email alerts
|

Preventable Deaths From Hemorrhage at a Level I Canadian Trauma Center

Abstract: Blunt injury is the major mechanism leading to trauma deaths. Massive bleeding from blunt pelvic injury is the major cause of preventable hemorrhagic deaths in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
144
2
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(156 citation statements)
references
References 21 publications
2
144
2
8
Order By: Relevance
“…[6] Rural civilian data indicate that approximately 10% of traumatic deaths are preventable [7] and 16% of preventable deaths are due to hemorrhage. [8] Hemorrhage is the second leading cause of death in trauma patients preceded only by traumatic brain injury. But hemorrhagic shock is the most common cause of preventable death within 6 hours of admission.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Rural civilian data indicate that approximately 10% of traumatic deaths are preventable [7] and 16% of preventable deaths are due to hemorrhage. [8] Hemorrhage is the second leading cause of death in trauma patients preceded only by traumatic brain injury. But hemorrhagic shock is the most common cause of preventable death within 6 hours of admission.…”
Section: Introductionmentioning
confidence: 99%
“…Actually according to the published reports, the preventable death has been markedly reduced from 20-23% to 2.5%. 3,6,19) Gruen et al 6) reported that 5.8% of all patients died in 9 years and 2.4% of them had recognized errors resulted in deaths. In their cases, 34% of errors had occurred in the ED; 20% initial assessment and resuscitation, 14% during the secondary survey and initial diagnostic test.…”
Section: Discussionmentioning
confidence: 99%
“…7,19) The mortality rate of patients with isolated head injuries has been reported about 11-30%, whereas in multiple traumas with head injuries mortality rates ran reach over 40%. 8,9,18) The authors reviewed the multiple trauma patients with traumatic brain injury who died in the emergency department and wanted to describe causes of death and to reconsider the role of neurosurgeons in association with trauma team.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier prospective clinical study from the same institute [9] described the population based epidemiology of pelvic ring fractures, and identified areas with potential for improvement. Despite all great efforts on bleeding control, these severe injuries still can cause exsanguination, which is the main cause of early mortality [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Major bleeding associated with HE-PRI is the main cause of early mortality associated [9,10]. Pelvic bleeding may originate from the broken bones, pelvic venous plexus, and named vessels and branches [1,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%